Evaluation of the mechanism of action of Bacillus spp. to manage Meloidogyne incognita with split root assay, RT-qPCR and qPCR - Gattoni, Kaitlin M.; Park, Sang Wook; Lawrence, Kathy S. (Frontiers in plant science, 2023)
The goal of this research is to determine the mechanism of action of two Bacillus spp. that can manage Meloidogyne incognita population density in cotton. The overall objectives are 1) determine the efficacy and direct antagonistic capabilities of the Bacillus spp. and 2) determine the systemic capabilities of the Bacillus spp. The greenhouse in planta assay indicated B. amyloliquefaciens QST713 and B. firmus I-1582 could manage M. incognita similarly to the chemical standard fluopyram. An in vitro assay determined that B. firmus I-1582 and its extracted metabolites were able to directly manage M. incognita second stage juveniles by increasing mortality rate above 75%. A split root assay, used to determine systemic capabilities of the bacteria, indicated B. amyloliquefaciens QST713 and B. firmus I-1582 could indirectly decrease the nematode population density. Another species, B. mojavensis strain 2, also demonstrated systemic capabilities but was not a successful biological control agent because it supported a high population density in greenhouse in planta assay and in the split root assay. A RT-qPCR assay was used to confirm any systemic activity observed in the split root assay. At 24 hours both B. amyloliquefaciens QST713 and B. firmus I-1582 upregulated one gene involved in the initial stages of JA synthesis pathway but not another gene involved in the later stages of JA synthesis. These results point to a JA intermediate molecule, most likely OPDA, stimulated by the bacteria rather than JA in a short-term systemic response. After 1 week, the Bacillus spp. stimulated a SA-responsive defense related gene. The long-term systemic response to the Bacillus spp. indicates salicylic acid also plays a role in defense conferred by these bacteria. The final assay was a qPCR to determine the concentration of the bacteria on the cotton roots after 24 days. Bacillus amyloliquefaciens QST713 and B. firmus I-43 1582 were able to colonize the root successfully, with the concentration after 24 days not significantly differing from the concentration at inoculation. This study identifies two bacteria that work via systemic resistance and will help aid in implementing these species in an integrated management system.